An Assessment of 21st-Century Skills Acquisition of Alternative Learning System (ALS) Senior High School Learners Towards the Development of Capacity Building Program - Hero, Jesson L. (Future Science / FSH-PH Publications, 2022)
The Alternative Learning System (ALS) has been found to be the new way for those who want to continue in their studies despite the challenges and current situation they are facing. Apparently however, there are studies recorded that there is a gap between the 21st-century skills of these ALS learners. With this concern, it becomes the notion of the researcher to describe and assess the 21st-century skills acquisition of enrolled Alternative Learning System Senior High School (ALS SHS) learners in one stand-alone public senior high school in the City of Meycauayan, Bulacan, for the School Year 2022-2023. The researcher made use of quantitative descriptive survey design to assess the 21st-century skills of 41 ALS SHS learners enrolled. Findings revealed that most of the respondents were female; in the age-range of 20-24 years old; and, have a monthly income of less than Php 5,000.00 a month. Alternative Learning System Senior High School (ALS SHS) learners had a moderate level of 21st-century skills acquisition. Furthermore, it showed that there is no significant difference on the 21st-century skills acquisition of ALS SHS learners when group according to gender and age-range, but there is a significant difference on the 21st-century skills acquisition of ALS SHS learners when group according to their socio-economic status (monthly income). For its recommendation, the proposed capacity building program aimed to improve further the Alternative Learning System Senior High School (ALS SHS) learners’ 21st-century learning skills and to jive on the current trends and challenges of 21st-century education despite of their struggles in life.